Establishing scheme and algorithm for dynamic key-path of pair wise key for sensor networks - HU Yu-zhou1; WANG Lei2; CHEN Zhi-ping2; GU Xue-dao3 (Tongxin xuebao)
Security schemes of pair wise key establishment ensure communication security in wireless sensor networks. Dynamic key-path in pair wise key establishment farther increases communication security in the networks. Establishing scheme and algorithm for dynamic key-path in pair wise key for wireless sensor networks were presented based on the encoding peculiarity and high fault-tolerant ability of named H（k,u,m,v,n） （hierarchical hypercube） of cluster distributed sensor networks. Theoretic studies and figures of computer simulation show that the algorithm has good reliability per- formance and high efficiency, which is suitable for cluster distributed sensor networks.